Effect of Thermal Cycling on the Structural Evolution of Methylammonium Lead Iodide Monitored around the Phase Transition Temperatures. Issue 7 (6th May 2019) - Glushkova, Anastasiia; Mantulnikovs, Konstantins; Giriat, Gaétan; Semeniuk, Konstantin; Forró, László; Horváth, Endre; Arakcheeva, Alla
Abstract : Optoelectronic devices and solar cells based on organometallic hybrid perovskites have to operate over a broad temperature range, which may contain their structural phase transitions. For instance, the temperature of 330 K, associated with the tetragonal–cubic transformation, may be crossed every day during the operation of solar cells. Therefore, the analysis of thermal cycling effects on structural and electronic properties is of significant importance. This issue is addressed in the case of methylammonium lead iodide (CH3 NH3 PbI3 ) across both structural phase transitions (at 160 and 330 K). In situ synchrotron radiation X‐ray diffraction (XRD) data recorded between 140 and 180 K show the emergence of a boundary phase between the orthorhombic and tetragonal phases, which becomes more abundant with successive thermal cycles. At high temperatures, around 330 K, an incommensurately modulated tetragonal phase is formed upon repeated crossings of the phase boundary between tetragonal and cubic phases. These alterations, which indicate a gradual evolution of the material under operating conditions of photovoltaic devices, are further documented by electrical resistivity and heat capacity measurements. Abstract : The structural and electronic properties after repeated thermal cycles around the phase transition in methylammonium lead iodide based on in situ synchrotron radiation X‐ray diffraction data, electrical resistivity, and heat capacity measurements are investigated. Data show the appearance of a boundary phase for thermal cycling around 160 K and the formation of an incommensurately modulated tetragonal phase around 330 K.